2018
DOI: 10.1159/000493419
|View full text |Cite
|
Sign up to set email alerts
|

Association of miR-197-5p, a Circulating Biomarker for Heart Failure, with Myocardial Fibrosis and Adverse Cardiovascular Events among Patients with Stage C or D Heart Failure

Abstract: Objective: The aim of this study was to identify heart failure (HF)-specific circulating micro-RNAs (miRNA), and examine whether the selected miRNAs correlate with myocardial fibrosis and are reflective of the incidence of adverse cardiovascular events in patients with stage C or D HF. Methods: Circulating miRNAs which were expressed in end-stage HF patients and matched healthy controls were detected by microarray analysis and validated by quantitative real-time polymerase chain reaction. Multivariate Cox regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…MiR-197-5p was demonstrated to act as circulating biomarker for heart failure [23]. It has been reported that in carcinogenesis of fibrosarcoma, miR-197-5p exerts its regulatory role through inhibiting of KIAA0101 [24].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-197-5p was demonstrated to act as circulating biomarker for heart failure [23]. It has been reported that in carcinogenesis of fibrosarcoma, miR-197-5p exerts its regulatory role through inhibiting of KIAA0101 [24].…”
Section: Discussionmentioning
confidence: 99%
“…Rubiś et al found that baseline serum levels of miR-21, miR-26, miR-29, and miR-30 were significantly different in DCM patients than in controls, and that MMP-2 levels were strongly associated with all of the microRNAs studied [137]. In a prospective study, elevated baseline plasma miR-197-5P levels were considered to be associated with myocardial fibrosis in patients with end-stage HF, and during the average 937-day follow-up period, 22 patients (27.5%) had major adverse cardiac events, including 19 deaths and three cardiac transplantations [138]. Additionally, multiple studies have found evidence implicating cardiac interstitial fibrosis in the deterioration of cardiac function in myocardial infarction.…”
Section: Gene Transcription (Mirna)mentioning
confidence: 98%
“…MiR-197-5p is upregulated in patients with cardiovascular disease and has been proposed as a biomarker for the prediction of cardiovascular events [52][53][54]. It is well established that patients with cardiovascular disease are overrepresented in symptomatic COVID-19 cohorts and have a higher mortality rate [55].…”
Section: Potential Interaction Of Sars-cov-2 Transcripts and Human MImentioning
confidence: 99%